Предмет: Алгебра,
автор: dana230708
-
1) 19 -(3x2 - 2x) - (6x - x2)= 7-2х2.
Ответы
Автор ответа:
0
x = 5
x = 5
x = 5
x = 5
x = 5
x = 5
x = 5
Автор ответа:
0
19 - (3х² - 2х) - (6х - х²) = 7 - 2х²
19 - 3х² + 2х - 6х + х² = 7 - 2х²
2х² + х² - 3х² - 4х = 7 - 19
-4х = -12
х = -12 : (-4)
х = 3
Ответ: 3.
Похожие вопросы
Предмет: Русский язык,
автор: лиана1982
Предмет: Английский язык,
автор: 123амина133
Предмет: Английский язык,
автор: indirarashidov
Предмет: Литература,
автор: burovvadim03
Предмет: Алгебра,
автор: serehr6426sb